2008
DOI: 10.1542/peds.2007-3453
|View full text |Cite
|
Sign up to set email alerts
|

Postdischarge Growth and Development in a Predominantly Hispanic, Very Low Birth Weight Population

Abstract: Very low birth weight infants exhibited growth patterns that coincided with developmental progress in the first 3 years of life. Birth at gestational age of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…As both preterm groups were comparable in neonatal morbidity, NICU nutritional management (and together to the third group with the breast milk intake), other causes such as nutritional, environmental, genetic (Powers et al, 2008) and post-natal growth factors (Fattal-Valeski et al, 2009) should be considered to explain the developmental differences in the IUGR group. In this regard, we found a characteristic pattern of poor weight, length and HC gain in the first year of life in preterm IUGR infants.…”
Section: Discussionmentioning
confidence: 99%
“…As both preterm groups were comparable in neonatal morbidity, NICU nutritional management (and together to the third group with the breast milk intake), other causes such as nutritional, environmental, genetic (Powers et al, 2008) and post-natal growth factors (Fattal-Valeski et al, 2009) should be considered to explain the developmental differences in the IUGR group. In this regard, we found a characteristic pattern of poor weight, length and HC gain in the first year of life in preterm IUGR infants.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] The causal pathway linking healthy prenatal practices and robust births by immigrant mothers seems to weaken for latergeneration Hispanic mothers. 6,7 Beyond the benefits of the epidemiological paradox for newborns, little is known about whether these benefits persist in health and cognitive domains during infancy. Social factors related to maternal practices and family poverty, especially for immigrant populations, may come to outweigh the biological advantages resulting from healthy births.…”
mentioning
confidence: 99%
“…It had an improvement until 30 months of age while growth disorder in neonates whose gestational age was ≤26 weeks was constant until the age of 3 years. [9] In the present study, growth pattern of subjects was investigated in a cross-section design, and contrary to Powers’ study, the subjects were evaluated ignoring their gestational age, so the results have the less predictive value which can be considered as a limitation of the present study.…”
Section: Discussionmentioning
confidence: 92%
“…In study of Power et al ., mean score of motor development in VLBW children with gestational age of ≥27 weeks was low in their infancy period while it improved at the age of 18 months, meanwhile in children with gestational age of ≤26 weeks, the developmental delay persisted until the age of 3 years. [9] Gutbrod et al ., investigated the effects of small for gestational age (SGA) in very low birth weight (VLBW) infants on growth and development until the fifth year of life, and showed that developmental test results were similar for the SGA and AGA-BW groups at 5 and 20 months. [13]…”
Section: Discussionmentioning
confidence: 99%